Effect of Drying Method on Quality of Soybean Seed (Bangladesh Agronomy Journal, 2015)
The experiment was conducted at the Seed Laboratory, Regional Agricultural Research Station, BARI, Jamalpur in 2010 with a view to study the effect of drying method on soybean seed germination and seedling vigour. Eight drying condition viz., i) Cemented floor ii) Tripale upon cemented floor iii) Bamboo chatai upon cemented floor, iv) Cloth upon cemented floor, v) Earthen floor, vi) Tripale upon earthen floor, vii) Bamboo chatai upon earthen floor and viii) Cloth upon earthen floor were included in the experimental treatment variables with three replications using a completely randomized design. Seed moisture content (%), germination (%), germination index, and seedling dry weight (g) were recorded at 50, 100, 150 and 200 days after storage (DAS). The highest germination percentage, germination index and seedling dry matter was obtained from tripale over cemented floor followed by bamboo chatai over cemented floor, tripale over earthen floor and bamboo chatai over earthen floor. The lowest germination percentage, germination index and seedling dry matter was obtained from cemented floor.Bangladesh Agron. J. 2015, 18(1): 53-57